A Dish Scheduling Model for Traditional Chinese Restaurants Based on Hybrid Multiple Criteria Decision-Making Algorithms and a Double-Layer Queuing Structure. (30th March 2022) - Huang, Feng; Chuang, Yen-Ching; Zhang, Yong-Hua; Lu, Bin; Xu, Hong-Lan
Abstract : This paper proposes a dish scheduling model for traditional Chinese restaurants based on hybrid multiple criteria decision-making (MCDM) algorithms and a double-layer queuing structure (DLQS). It simulates real-world dish scheduling and may be universally applied. First, several factors that affect the dish ranking were identified, and their weights were determined. Subsequently, a modified Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) was used to rank the dishes and enhance the ranking stability after classifying the dishes based on system preset categories. A DLQS was designed to transfer the dishes from the top layer of the queue to the bottom of the queue according to certain rules, so that they could be processed and served in the correct order. The case study indicates that this model may help in the automation of dish scheduling and improve overall customer satisfaction.